Fancy Creek, Clay County - Cook, Kevin (Kansas State University, The Chapman Center for Rural Studies, 2011)
Fancy Creek was not a town at all, but a loose collection of settler homesteads in a township originally named Goshen. Goshen Township was first established and settled on March 18th, 1860 by Capt. G. Shaubel and others who came from the town of Goshen, Indiana. The first settlement along Fancy Creek itself was made by a man named Gabriel Spurrier in March of 1860.
Kevin Cook, “Fancy Creek, Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/62.
Keywords: Capt. G Shaubel; Chapman's Creek; Fancy Creek; Timber Creek; Pete's Creek; Deep Creek